Banjir dan Kerusakan Ekologis di Cimuncang, Serang Banten: Analisis Tafsir Ilmi Terhadap Keterkaitan Wahyu dan Fenomena Alam - Herlina, Herlina; Nurlaila, Siti; Latief, Dani Abdu; Bayyinahdy, Julfathra; Rosa, Andi (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
This article examines the integration between the text of revelation and ecological phenomena through a scientific interpretation approach, focusing on the case of floods in Cimuncang, Serang, Banten. This research is motivated by the increasing frequency of ecological disasters that require a rereading of the verses of the Qur'an contextually and based on field data. Using a qualitative-descriptive approach, this study combines the analysis of ecological verses in the Qur'an with empirical data from observations, in-depth interviews, and visual documentation in the affected areas. The approach of scientific interpretation is applied systematically through four methodological stages: integrative conception, the main provisions of interpretation, theoretical and technical principles, and the selection of relevant methods. The results of the study show that the Cimuncang flood is the result of structural violations of the ecological principles mentioned in the Qur'an, such as the caliphate's mandate, balance (mīzān), and the prohibition of fasād. Geographic vulnerability is also a cause of flooding. In this situation, the interpretation of science not only adds to the hermeneutic insights of the Qur'an, but also offers a transformational paradigm that connects Islamic science and environmental science. As an ethical-spiritual foundation for formulating sustainable development policies and ecological disaster mitigation, locality-based, participatory, and systemic interpretations are needed. Therefore, scientific interpretation not only serves as a tool of interpretation but also as an epistemological strategy to respond to the complexity of the world's environmental crisis.